2020
DOI: 10.4168/aair.2020.12.4.669
|View full text |Cite
|
Sign up to set email alerts
|

Lung Disease Diagnostic Model Through IgG Sensitization to Microbial Extracellular Vesicles

Abstract: Purpose: Recently, there has been a rise in the interest to understand the composition of indoor dust due to its association with lung diseases such as asthma, chronic obstructive pulmonary disease (COPD) and lung cancer. Furthermore, it has been found that bacterial extracellular vesicles (EVs) within indoor dust particles can induce pulmonary inflammation, suggesting that these might play a role in lung disease. Methods: We performed microbiome analysis of indoor dust EVs isolated from mattresses in apartmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…This information should contribute to knowledge of the involvement of lung microbiome in the development of COPD. Yang et al [ 39 ] demonstrated that the levels of antibacterial EV IgG antibodies were higher in patients with asthma and COPD compared to the healthy controls and we provided a lung disease diagnostic model based on antibacterial EV antibody titers.…”
Section: Summary and Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This information should contribute to knowledge of the involvement of lung microbiome in the development of COPD. Yang et al [ 39 ] demonstrated that the levels of antibacterial EV IgG antibodies were higher in patients with asthma and COPD compared to the healthy controls and we provided a lung disease diagnostic model based on antibacterial EV antibody titers.…”
Section: Summary and Discussionmentioning
confidence: 96%
“…Yang et al [ 39 ] performed microbiome analysis of indoor dust EVs isolated from mattresses in apartments and hospitals. We developed diagnostic models based on the bacterial EVs antibodies detected in serum samples via enzyme-linked immunosorbent assay.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies [31][32][33][34] investigated whether bacteria-derived EVs were related to COPD (Table 5a). Three research articles [32][33][34] identi ed carried out ex vivo human studies and one study [31] was done in vivo using a mice model and additionally in vitro assays. Kim, Y.S., et al [31] determined that EVs derived from bacteria resulted in emphysema due to neutrophilic in ammation.…”
Section: Bacterial Evs and Copdmentioning
confidence: 99%
“…Three [32][33][34] of the studies were assessed and scores ranged from 0.50 to 0.64. Breakdown of their assessment can be noted in table 5b.…”
Section: Bacterial Evs and Copdmentioning
confidence: 99%